Hubungan Antara Tingkat Aktivitas Fisik Harian dengan Status Gizi pada Remaja di SMA Batik 1 Surakarta - Melati Pujianti; Muwakhidah Muwakhidah; Nur Lathifah Mardiyati (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Nutritional problems among adolescents, such as undernutrition, overnutrition, and obesity, remain public health challenges that require attention. According to the 2018 Riskesdas survey, the prevalence of overnutrition among adolescents aged 16–18 years reached 9.5%, with physical activity being one of the factors that play a role in maintaining the body’s energy balance. This study aims to analyze the relationship between daily physical activity levels and nutritional status among adolescents at Batik 1 High School in Surakarta. The theoretical framework used includes the concept of adolescent nutritional status based on the Age-Adjusted Body Mass Index (BMI/A) as well as Brown’s (2005) modified theoretical framework. This study employed an analytical observational design with a cross-sectional approach. The study sample consisted of 62 11th-grade students selected using simple random sampling. Nutritional status data were obtained through anthropometric measurements, while physical activity levels were assessed using the Physical Activity Questionnaire for Adolescents (PAQ-A). The results showed that the majority of respondents had an overnutrition status (50%) and moderate physical activity levels (50%). Analysis using Spearman’s rank correlation test yielded a p-value of 0.188 (p > 0.05), indicating no significant association between physical activity and nutritional status. These findings suggest that adolescents’ nutritional status is influenced by various factors other than physical activity, such as dietary patterns, energy intake, and lifestyle behaviors.